Plasma B vitamins and LINE‐1 DNA methylation in leukocytes of patients with a history of colorectal adenomas. Issue 4 (7th November 2012) - Jung, Audrey Y.; Botma, Akke; Lute, Carolien; Blom, Henk J.; Ueland, Per M.; Kvalheim, Gry; Midttun, Øivind; Nagengast, Fokko; Steegenga, Wilma; Kampman, Ellen; Ulrich, Cornelia M.; Miller, Joshua W.
<x xml:space="preserve">Abstract</x> Scope Low concentrations of folate, other B vitamins, and methionine are associated with colorectal cancer risk, possibly by changing DNA methylation patterns. Here, we examine whether plasma concentrations of B vitamins and methionine are associated with methylation of long interspersed nuclear element‐1 (LINE‐1) among those at high risk of colorectal cancer, i.e. patients with at least one histologically confirmed colorectal adenoma (CRA) in their life. Methods and results We used LINE‐1 bisulfite pyrosequencing to measure global DNA methylation levels in leukocytes of 281 CRA patients. Multivariable linear regression was used to assess associations between plasma B vitamin concentrations and LINE‐1 methylation levels. Plasma folate was inversely associated with LINE‐1 methylation in CRA patients, while plasma methionine was positively associated with LINE‐1 methylation. Conclusion This study does not provide evidence that in CRA patients, plasma folate concentrations are positively related to LINE‐1 methylation in leukocytes but does suggest a direct association between plasma methionine and LINE‐1 methylation in leukocytes.